The Impact of The Internet on Economic Growth In UE15 (2006-2020) – A Panel Data Analysis - Anna GALIK (Communications of International Proceedings, 2021)
This paper explores the impact of the Internet on economic growth. A panel data analysis was conducted for UE 15 countries (Austria, Belgium, Denmark, Finland, France, Greece, Spain, the Netherlands, Ireland, Luxembourg, Germany, Portugal, Sweden, the United Kingdom and Italy). The research covers a period of 15 years from 2006 to 2020 based on OECD data. In the result, the conducted research provides the unexpected conclusion. Although an analysis of the literature indicates a significant impact of the Internet on economic growth the quantitative analysis shows there is some evidence of a positive impact of Internet coverage on the GDP growth, but the registered influence is not considerably strong.
Keywords: Economic Growth; Gross Domestic Product (GDP); New Technology; Internet